Relationship Between Economic Growth And the Environment In the Czech Regions - Lešáková, Petra; Šatera, Karel; Brodský, Zdeněk (Univerzita Tomáše Bati ve Zlíně, 2017)
This paper deals with the sustainability assessment and the sustainability performance, because sustainability performance measurement is crucial in sustainability development planning. Aim of this study is not to encompass the whole issue of measurement of sustainable development. The aim of this paper is to provide a clear picture about relationship between economic growth and the environment in the regions of the Czech Republic between 2000 and 2014 by using method of decoupling. This paper uses selected real regional data to demonstrate a practical use of method of decoupling as a tool for evaluation of environmental sustainability performance over time on regional level, because regional level is supposed to play vitally important role in achieving sustainable development goals. Moreover, provided analysis also compare regions of the Czech Republic based on the calculated values - level of decoupling. Besides others, analysis shows that economies of the regions of the Czech Republic can be characterized as creating more value using fewer resources and generating less waste and pollution over time.
Vztah mezi ekonomickým rozvojem a životním prostředí regionů ČR
Keywords: decoupling; economic growth; ecological modernization; environmental sustainability; regions of the Czech Republic; Decoupling; ekonomický růst; ekologická modernizace; environmentální udržitelnost; regiony ČR